Pengaruh Pijat RPS ( Reverse Presure Softening ) dan Pemberian Gel Aloe Vera terhadap Pembengkakan dan Penurunan Nyeri Payudara Pada Ibu Dengan Bendungan ASI - Saidah, Halimatus; Prasetyanti , Dhita Kris; Wigati , Putri Wahyu; Sutrisni (Jurnal Keperawatan Muhammadiyah, 2024)
Objective:: Breastfeeding is the best way to provide ideal nutrition for baby's growth and development, but not all mothers experience a smooth breastfeeding process, one of which is swelling/breast milk dams due to narrowing of the lacteferi ducts. Mothers with breast milk dams are often confused about how to handle them so that they will have a worse impact, becoming mastitis or even breast abscesses. Breast milk dams occur in 72% to 82% of breastfeeding women, the RPS (Reverse Pressure Softening) technique and compresses using aloe vera can be an alternative treatment. The purpose of this study was to determine the Effect of RPS (Reverse Pressure Softening) Massage and Aloe Vera Gel Administration on Breast Swelling and Reducing Breast Pain in mothers with engorgment in the Sukorame Health Center Work Area in 2024. Methods: The design in this study was a study with the type of Pretest Posttest With Control Group Design. The population in this study were breastfeeding mothers who experienced breast milk engorgement on days 3-11 postpartum (transitional breast milk phase), determination of breast milk engorgement using SPES (Six Point Engorgement Scale), a sample of 32 respondents. Sampling was done by Purposive Sampling. Data collection techniques were carried out by interviews and observations using the Numeric Rating Scale (NRS) questionnaire for pain measurement and breast engorgement assessment points using the Six Point Engorgement Scale (SPES). Data were analyzed using Man Whitney Results: the results of statistical tests using the Man-Whitney test showed a significant difference between the engorgement scale, the breast pain intensity scale, between the RPS (Reverse Pressure Softening) Massage intervention group and Cold Compress using aloe vera gel. The engorgement scale has a ρ value of 0.000; the pain intensity scale has a ρ value of 0.001 (ρ value <0.05) so that there is an effect of the Use of RPS (Reverse Pressure Softening) Massage and Aloe Vera Gel Compress on the Breast Swelling scale and pain intensity scale Conclusion: there is an effect of the Use of RPS (Reverse Pressure Softening) Massage and Aloe Vera Gel Compress on the Breast